Host variation in Pinus radiata in response to inoculation with Neonectria fuckeliana - Dick, M.A.; Hopkins, A.J.M.; Power, M.W.P. (New Zealand Plant Protection, 2008)
Neonectria fuckeliana causes a stem canker (Nectria flute canker) of plantationgrown Pinus radiata in southern regions of the South Island of New Zealand Initiation of disease is primarily associated with pruning operations and modification of pruning regimes has led to a reduction in disease incidence Factors that influence establishment of infection and symptom expression are being examined In one trial in which 50 trees were challenged with three different conidial concentrations individual trees varied markedly in their response to inoculation Twentytwo percent of controls (wounds inoculated with sterile water) developed depressions that resembled small cankers Six percent of the trees did not develop cankers at any concentration when inoculated with conidiospore solutions Fortyeight percent responded with increasing canker length with increasing dose and in 26 of trees severe cankering developed at all inoculum concentrations Perithecial formation on the cankers was correlated with canker severity Host genotype is being examined further with the goal of identifying families that contribute to susceptibility to canker formation